Sustainability goals and project success from the perspective of the stakeholders of green building project in Malaysia: a preliminary study - Mohd Isa, Nor Kalsum; Mohd Yunos, Mohd Yazid; Ismail, Kamarul; Marzuki, Mazdi (Universiti Pendidikan Sultan Idris, 2018)
Green building is an emerging concept with the ultimate target to achieve sustainable development. Many studies revealed that the building project had contributed towards sustainability and project success in the past. The purpose of this study was to determine the advantages of sustainable application in building projects, looking towards project success from the perspective of Malaysian project stakeholders and to explore the establishment of sustainability goals in the green building projects in Malaysia. The Triple Bottom Line Concept of Sustainability (TBL) was used as the foundation of the theoretical framework. Quantitative, qualitative and multiple case study methods were employed. A sample of 188 Malaysian building project stakeholders was selected for questionnaire surveys, and 15 stakeholders from three award-winning green building projects in Malaysia were involved in the interviews. The quantitative data was analysed using descriptive statistic. Meanwhile, cross case analysis and literal replication logic were utilized for the multiple case study and qualitative analysis. The study found that majority of the respondents believed that the development of a green building project impacts more on the quality enhancement aspect of the building as compared to others. The goal of achieving environmental sustainability was given more priority than the other goals throughout the development of the green buildings.